RETRACTED: Modernization of electronic document management and systems analysis processes using an automated platform - Panfilova Tatyana; Tynchenko Vadim; Kukartseva Oksana; Kozlova Anastasia; Glinscaya Anna (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001